A short term anatomical and visual outcomes of large idiopathic macular holes surgery following inverted internal limiting membrane flap technique - Shakya, Kiran; Pokharel, Ram Prasad; Malla, Om Krishna (Nepalese Journal of Ophthalmology, 2019)
Introduction: Large macular holes are not uncommon among Nepalese women population causing severe visual problem.Objective: To evaluate the technique of inverted internal limiting membrane (ILM) flaps for the repairment of large macular holes.Methods: All 10 macular holes (diameter > 400 μm) were treated with pars planavitrectomy with inverted ILM flap technique. The procedure for macular hole surgerywas pars plana vitrectomy, posterior vitreous removal, internal limiting membrane(ILM) peeling with brilliant blue assisted, inverting ILM flap into macular hole, filling of the vitreous cavity with a gas bubble(C3 F8) and post-operative face-down positioning for 1 week. SD OCT images were taken preoperative and postoperative 1 month and 3 months follow up to assess the anatomical outcome of surgery and best corrected visual acuity (BCVA) was used to evaluate the functional outcome during each visit. The BCVA was recorded using the Snellen chart and was converted to the logarithm of the minimum angle of resolution (LogMAR) equivalents.Results: All 10 eyes had complete anatomical closure. The mean age of patients was 64.3 ± 7.53 years. The mean macular hole base diameter was 1039.4 μm (663-1526μm). Mean BVCA pre-operatively was 1.29 log MAR ±SD 0.25. Post-operatively, mean BCVA was 0.925 log MAR ±SD 0.143 (p= 0.002). There were no intra operative or post-operative complications. All the patients were followed up for a period of 3months.Conclusions: Inverted ILM flaps is effective for closure of the large macular hole and restoration of functional vision.